A dynamic pedicle screw system using polyethylene insert for the lumbar spine. Issue 4 (18th November 2022) - Oshima, Yasushi; Kato, So; Doi, Toru; Taniguchi, Yuki; Matsubayashi, Yoshitaka; Ohtomo, Nozomu; Watanabe, Kenichi; Kyomoto, Masayuki; Tanaka, Sakae; Moro, Toru
Abstract: Rigid spinal fusion with instrumentation has been widely applied in treating degenerative spinal disorders and has shown excellent and stable surgical results. However, adjacent segment pathology or implants' loosening could be problematic due to the spine's segmental fusion. Therefore, this study verified a novel concept for posterior stabilization with polyethylene inserts inside a pedicle screw assembly using bone models. We observed that although the gripping capacity of the dynamic pedicle screw system using a tensile and compression tester was less than half that of the rigid pedicle screw system, the flexion‐extension moment of the dynamic pedicle screws was significantly lower than that of the rigid pedicle screws. Furthermore, while the bending force of the rigid pedicle screw assembly increased linearly with an increase in the bending angle throughout the test, that of the dynamic pedicle screw assembly also increased linearly until a bending angle of 2.5° was reached. However, this angle decreased at a bending angle of more than 2.5°. Additionally, the fatigue test of 1.0 × 10 6 cycles showed that the pull‐out force of the dynamic pedicle screws from two different polyurethane foam blocks was significantly higher than that of the rigid pedicle screws. Therefore, based on our results, we propose that the device can be applied in clinical cases to reduce screw loosening and adjacent segment pathology.